Grid routing: an energy-efficient routing protocol for WSNs with single mobile sink. (2017) - Liu, Qi; Zhang, Kai; Liu, Xiaodong; Linge, Nigel
In a traditional wireless sensor network (WSN) with static sinks, sensor nodes close to the sink run out of their batteries quicker than other nodes due to the increased data traffic towards the sink. These nodes with huge data traffic are easy to become hotspots. Therefore, such networks may prematurely collapse since the sink is unreachable for other remote nodes. To mitigate this problem, sink mobility is proposed, which provides load-balanced data delivery and uniform energy dissipation by shifting the hotspots. However, the latest location update of the mobile sink within the network introduces a high communication overhead. In this paper, we propose Grid Routing, an energy-efficient mobile sink routing protocol, which aims to decrease the advertisement overhead of the sink's position and balance local energy dissipation in a non-uniform network. Simulation results indicate that the Grid Routing shows better performance compared with existing work.